UPAYA GURU BIMBINGAN DAN KONSELING MENGATASI KECEMASAN BERBICARA DI DEPAN UMUM - Armaichi, Ella; Mudaim, Mudaim; Pranoto, Hadi (Universitas Muhammadiyah Metro, 2023)
The aims of this study were To describe the Public Speaking Anxiety of students at SMP Muhammadiyah Al Ghifari Batanghari. To find out the efforts of Guidance and Counseling Teachers on Public Speaking Anxiety in Studen SMP Muhammadiyah Al Ghifari Batanghari. The desain of this research is a qualitative research using the interview method. The presence of the researcher as a data collector as well as analyzing the data. The instrumen in this study used interview sheets, observation and documentation. Data analysis used descriptive inductive data analysis. The conclusion of this study is to look at the description of anxiety experienced by students and see the efforts made by Guidance and Counseling Teachers in Reducing Speaking Anxiety students show that speaking anxiety begins to decrease and students are no longer shaking or nervouse when asked to speak in public speaking (class). In other words this study showed positive results for seventh grade students of SMP Muhammadiyah Al Ghifari Batanghari who experienced public speaking anxiety.